2018
DOI: 10.20944/preprints201805.0024.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Investigation on Virtual Information Modeling Acceptance Based on Project Management Knowledge Areas

Abstract: In the contemporary construction management, poor project performance, cost overrun, and low-quality construction have become a central point of attention for improving project performance including information, interaction and communication management. virtual design and construction and building information modelling play indispensable role in improving the project performance. The aim of this study is to propose a Virtual Information Modeling as a novel information and communication technology method with p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…The literature needs to explore and evaluate the way that digital technologies can be utilized to improve productivity and safety in construction projects. A list of technologies that have received attention in the literature include: building information modelling; virtual and augmented reality; mobile and wearable technologies; LiDAR technology; automated material identification; real-time locating and tracking systems; GPS-guided plant and machinery [7,15,[50][51][52]. In this study, 'construction technology' refers to any tool, plant or equipment used for carrying out physical construction activities, and advanced technology refers to the latest models of such a plant and equipment.…”
Section: Construction Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The literature needs to explore and evaluate the way that digital technologies can be utilized to improve productivity and safety in construction projects. A list of technologies that have received attention in the literature include: building information modelling; virtual and augmented reality; mobile and wearable technologies; LiDAR technology; automated material identification; real-time locating and tracking systems; GPS-guided plant and machinery [7,15,[50][51][52]. In this study, 'construction technology' refers to any tool, plant or equipment used for carrying out physical construction activities, and advanced technology refers to the latest models of such a plant and equipment.…”
Section: Construction Technologymentioning
confidence: 99%
“…For example, adding vibration to the rolling action of compactors exhibited a 260% increase in productivity during the mid-1980s when this technology was introduced by Caterpillar [11]. This leads to a growing focus on introducing new technologies [4,[12][13][14][15] to the construction industry by various firms in order to benefit from such advantages [16,17]. According to Goodrum et al [18], awareness of a particular technology does not ensure its adoption, and a "series of interrelated events" is required for the success of its implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Our experimentation revealed that a combination of algorithms can help to provide fairly accurate information about the quality of panels during construction. Our experimentation also assists draftsmen for as-built modelling and updating Building Information Modeling [69][70][71], based on the final panel layout and joint sizes. The construction industry has been known to be laggard in adopting new technologies, and there is a large effort to facilitate the process of technology adoption by exploring new applications and addressing barriers of technology implementation [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…The literature needs to explore and evaluate the way that digital technologies can be utilized in a way to improve productivity and safety in construction projects. A list of technologies that has received attention in the literature include: building information modelling, virtual and augmented reality; mobile and wearable technologies; lidar technology, automated material identification; real time locating and tracking systems; GPS guided plant and machinery [7,15,[51][52][53][54]. In this study, 'construction technology' refers to any tool, plant or equipment used for carrying out physical construction activities, and advanced technology refers to the latest models of such plant and equipment.…”
Section: Construction Technologymentioning
confidence: 99%
“…For example, adding vibration to the rolling action of compactors exhibited a 260% increase in productivity during the mid-1980s when this technology was introduced by Caterpillar [11]. This leads to a growing focus on introducing new technologies [4,[12][13][14][15] to the construction industry by various firms in order to benefit from such advantages [16,17]. According to Goodrum et al [18], awareness of a particular technology does not ensure its adoption, and a "series of interrelated events" is required for the success of its implementation.…”
Section: Introductionmentioning
confidence: 99%